2020
DOI: 10.3390/geriatrics5010016
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-Based Role of Nutrients and Antioxidants for Chronic Pain Management in Musculoskeletal Frailty and Sarcopenia in Aging

Abstract: Musculoskeletal disorders in aging and pain are closely connected because of multiple mechanisms leading to loss of mobility and autonomy. Pain is predictive of diability and worsening frailty and the strength of this relationship increases with the severity of pain. This study presents a systematic review of randomized controlled trials, cross sectional studies, and observational studies based on treatment of pain in adults with musculoskeletal disorders using nutritional non-pharmacological (nutrients and an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 48 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…These three products are widely used as dietary supplements [ 36 , 37 , 38 , 39 ]. In the meantime, the literature gives examples of numerous dietary supplements that could successfully prevent or alleviate the progression of muscle mass loss in old age [ 40 , 41 , 42 ]. Bee products represent a part of this interventional strategy.…”
Section: Apitherapy As a Possible Complementary Treatment For Sarcmentioning
confidence: 99%
“…These three products are widely used as dietary supplements [ 36 , 37 , 38 , 39 ]. In the meantime, the literature gives examples of numerous dietary supplements that could successfully prevent or alleviate the progression of muscle mass loss in old age [ 40 , 41 , 42 ]. Bee products represent a part of this interventional strategy.…”
Section: Apitherapy As a Possible Complementary Treatment For Sarcmentioning
confidence: 99%
“…Endorphins are a group of endogenous opioid neuropeptides which are stronger than morphine as pain relievers. Some studies have observed that the consumption of 90-100 g of protein per day prevents neurotransmitter depletion and significant muscle-wasting [94]. A significant positive association between protein intake and pain threshold was reported among patients with fibromyalgia.…”
Section: High-protein Dietmentioning
confidence: 99%
“…Several nutritional interventions are reported to prevent or revert sarcopenia and related muscle fatigue. High protein diets are of particular importance; healthy active individuals require, at least, 1.0-1.2 g of protein/kg body weight/day while the need for protein in sarcopenic individuals is even greater (1.2-1.5 g/kg body weight/day) [41,46,138]. Older individuals are resistant to refeeding i.e., recovering their nutritional deficiency is slower and more difficult than in younger ages [133].…”
Section: Nutritional Deficiencymentioning
confidence: 99%
“…Other dietary elements that can slow sarcopenia include creatine-rich food (e.g., fish and meat), glutamic acid-rich food (e.g., soy and egg), tryptophan-rich food (e.g., milk and peanuts), long-chain polyunsaturated fatty acids (e.g., fish oil), vitamin D, and antioxidant supplements (e.g., selenium, vitamin A, vitamin C, vitamin E, and β-carotene) [41,46,138]. However, purified antioxidant supplements may become pro-oxidants when they overactivate the NRF2/antioxidant response element (ARE) antioxidant system, which is associated with serious adverse effects including cancer and mortality [5,143].…”
Section: Nutritional Deficiencymentioning
confidence: 99%